2022
DOI: 10.3390/antiox11122353
|View full text |Cite
|
Sign up to set email alerts
|

Phloroglucinol Attenuates DNA Damage and Apoptosis Induced by Oxidative Stress in Human Retinal Pigment Epithelium ARPE-19 Cells by Blocking the Production of Mitochondrial ROS

Abstract: Phloroglucinol, a phenolic compound, is known to possess a potent antioxidant ability. However, its role in retinal cells susceptible to oxidative stress has not been well elucidated yet. Thus, the objective of this study was to evaluate whether phloroglucinol could protect against oxidative damage in cultured human retinal pigment epithelium ARPE-19 cells. For this purpose, ARPE-19 cells were stimula ted with hydrogen peroxide (H2O2) to mimic oxidative stress. Cell viability, cytotoxicity, apoptosis, reactive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 64 publications
2
5
0
Order By: Relevance
“…Therefore, we investigated whether PG has anti-oxidative abilities in HDPCs. Consistent with previous studies, our data showed that PG reduced ROS levels in HDPCs [ 35 , 112 ]. Additionally, when HDPCs were exposed to H 2 O 2 and then treated with PG, both oxidative stress markers ( HMOX1 and SOD1 ) and senescence markers ( p16 and p21 ) were significantly alleviated.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, we investigated whether PG has anti-oxidative abilities in HDPCs. Consistent with previous studies, our data showed that PG reduced ROS levels in HDPCs [ 35 , 112 ]. Additionally, when HDPCs were exposed to H 2 O 2 and then treated with PG, both oxidative stress markers ( HMOX1 and SOD1 ) and senescence markers ( p16 and p21 ) were significantly alleviated.…”
Section: Discussionsupporting
confidence: 93%
“…In a mouse model of diabetes, activation of GLP-1R has been shown to alleviate depressed behaviors by decreasing the level of ROS to improve mitochondrial functions and promote mitophagy [ 5 ]. In retinal pigment epithelium exposed to hydrogen peroxide, DNA damage and apoptosis are associated with inhibited mitophagy, which could be reversed by downregulating the level of ROS [ 6 ]. Collectively, available findings suggest that enhancing mitophagy exhibits beneficial outcomes via blocking of ROS production and accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…One major event during apoptosis is the escape of cytochrome-C (cyt-C), a highly conserved mitochondrial hemeprotein vital to electron transport and cellular respiration [ 60 ]. Transit of cyt-C into cytosol can occur through a membrane channel controlled by the first regulator of apoptosis to be identified in any organism, Bcl-2.61 Bcl-2 thus exerts an anti-apoptotic function by conserving membrane potential via blocking release of cyt-C [ 61 , 62 ].…”
Section: Subcellular Characteristics After Prpmentioning
confidence: 99%